EUCALYPTUS PLANTATION IN THAILAND - Thaiutsa, Bunvong; Taweesuk, Siripun (วารสารวนศาสตร์ไทย, 2022)
Althrough eucalypt was introduced to be planted at Prae province in the North in 1946, large-scale plantations were established less than a decade. Eucalyptus species in Thailand has been referred only to Eucalyptus camaldulensis. The total areas planted up to the end of 1986 were of 334,532 rai, nearly 10 percent of the country's man-made forest. Almost one third of the existing eucalyptus plantation owned by private sector, mainly for export as woodchip. Based on the current stumpage price of 450 baht per ton of wood, only plantation located within the radius of 200 km from woodchip factory would be economically viable. Cost of plantation for 5-year rotation was found to be 2,677 baht per rai with an annual net profit of 815 baht per rai. It was a policy of the Ministry of Agriculture and Cooperatives to continue promoting eucalyptus planting, especially on unproductive sites.